PC Splice-Site Variant c.1825+5G>A Caused Intron Retention in a Patient With Pyruvate Carboxylase Deficiency: A Case Report - Tao, DongYing; Zhang, HuiQin; Yang, Jingmin; Niu, HuanHong; Zhang, JingJing; Zeng, Minghua; Cheng, ShengQuan (Frontiers in Pediatrics, 2022)
Background: Pyruvate carboxylase deficiency (PCD; MIM＃266150) is a rare autosomal recessive disorder characterized by a wide range of clinical features, including delayed neurodevelopment, elevated pyruvate levels, lactic acidosis, ketosis, and hyperammonemia. Pyruvate carboxylase (PC) gene was identified to be the disease-causing gene for PCD. A novel homozygous splice variant in the PC gene was identified in a Chinese boy, but the pathogenicity is still unclear. The objective of the present study was to determine the effect of this splice-site variant by reverse transcription analysis. Methods: We report the clinical course of a 20-month-old Chinese pediatric patient who was diagnosed with PCD using whole-exome sequencing (WES). The effects of the variant on mRNA splicing were analyzed through transcript analysis in vivo. Results: The results of metabolic blood and urine screening, using tandem mass spectrometry, suggested PCD; WES revealed a novel homozygous splice-site variant (c.1825+5G>A) in the PC gene. In vivo transcript analysis indicated that the splice-site variant caused the retention of 192 bp of intron. Conclusion：Thus, c.1825+5G>A was established as a pathogenic variant, thereby enriching the mutational spectrum of the PC gene and providing a basis for the genetic diagnosis of PCD.